(NpERWYE [AGI SOCIALISTI^ESKOGO PEREUSTROJSTWA SELXSKOGO HOZQJSTWA W (B1918-1920 (NGG(B. /s - (NsKRYPNEW(B, (Nns ((NmOSKW(Ba :s (NgOSPOLITIZDAT(B,s, 1951)
(NzAKL(B.: (NS(B. 82-93s
Keywords: (NsOCIALISTI^ESKAQ SISTEMA HOZQJSTWAs